Crafting Prehispanic Maya Kinship - Ensor, Bradley E., 1966- (Book collections on Project MUSE., 2013)
By contextualizing classes and their kinship behavior within the overall political economy, Crafting Prehispanic Maya Kinship provides an example of how archaeology can help to explain the formation of disparate classes and kinship patterns within an ancient state-level society. Bradley E. Ensor provides a new theoretical contribution to Maya ethnographic, ethnohistoric, and archaeological research. Rather than operating solely as a symbolic order unobservable to archaeologists, kinship, according to Ensor, forms concrete social relations that structure daily life and can.